Stability, chaos and multiple attractors: A single agent makes a difference - Tamotsu Onozaki; Gernot Sieg; Masanori Yokoo (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2001)
This paper provides an example in which a slight behavioral heterogeneity may fundamentally change the qualitative properties of a nonlinear cobweb market with a quadratic cost function and an isoelastic demand function. We consider two types of producers; adaptive and naive. In a market of naive agents a single adaptive agent stabilizes the otherwise exploding market. In a market of adaptive agents a single naive agent may destabilize the market; without him there exists at most one periodic attractor in the market but with him there may appear many coexisting periodic attractors of arbitrarily large periods.
Keywords: D21; E32; C61; 330; 2-D Nonlinear cobweb model; Behavioral heterogeneity; Chaos; Homoclinic bifurcations; Coexisting periodic attractors; Cobweb; Erwartungstheorie; Chaostheorie; Theorie; Nichtlineare dynamische Systeme